The impact of regulatory heterogeneity on global value chain-related trade - Alessio Lombini (University of Neuchâtel, Institute of Economic Research (IRENE), 2021)
In this paper, I estimate the impact of heterogeneity in non-tariff-measures (NTMs) policies on countries' global value chains (GVCs)-related trade and its backward and forward components. I firstly build a regulatory distance (RD) index, which measures the degree of dissimilarity in NTMs structures between two trade partners. By including the RD index in a structural gravity model, I then find a significant negative effect of regulatory distance on total, backward, and forward GVC-related trade. The negative impact results to be even stronger when I conduct the analysis only on manufacturing sectors. On the country dimension, I demonstrate that the effects of regulatory distance are associated with the exporters' and the importers' income levels.
Keywords: E16; F13; F14; F15; F63; L51; O40; 330; Gravity equation; non-tariff measures; regulatory distance; trade protection; international trade; global value chains; technical regulations